Patritumab plus trastuzumab and paclitaxel in human epidermal growth factor receptor 2‐overexpressing metastatic breast cancer. Issue 10 (15th September 2016) - Mukai, Hirofumi; Saeki, Toshiaki; Aogi, Kenjiro; Naito, Yoichi; Matsubara, Nobuaki; Shigekawa, Takashi; Ueda, Shigeto; Takashima, Seiki; Hara, Fumikata; Yamashita, Tomonari; Ohwada, Shoichi; Sasaki, Yasutsuna
Abstract : Human epidermal growth factor receptor 3 (HER3) expression in lung and breast cancers has a negative impact on survival. Patritumab, a human anti‐HER3 mAb, has shown anticancer activity in preclinical models. This study examined the safety and pharmacokinetics of patritumab in combination with trastuzumab and paclitaxel in patients with HER2‐overexpressing metastatic breast cancer. In this open‐label, multicenter, dose‐escalation, phase Ib study, patients received patritumab 9 or 18 mg/kg plus trastuzumab and paclitaxel at known tolerated doses. Safety and tolerability were assessed based on dose‐limiting toxicities and other non‐life threatening adverse events. The pharmacokinetic profile for patritumab was determined based on the target trough level. Clinical efficacy was evaluated based on the overall response rate and progression‐free survival. Six patients received patritumab 9 mg/kg and 12 received 18 mg/kg. The most common adverse events were diarrhea, alopecia, leukopenia, neutropenia, and maculopapular rash. No dose‐limiting toxicities were observed. The target trough serum concentration was achieved in all patients at a dose of 18 mg/kg. Overall response rate was 38.9% and median progression‐free survival was 274 days. In conclusion, patritumab plus trastuzumab and paclitaxel was tolerable and efficacious at both doses. We recommend the dose level of 18 mg/kg for future phase II studies. (Clinical trial registration: JapicCTI‐121772.) Abstract : We examined the safety and pharmacokinetics of patritumab, a human anti‐HER3 monoclonal antibody that has shown anticancer activity in preclinical models, in combination with trastuzumab and paclitaxel in patients with HER2‐overexpressing metastatic breast cancer. No dose‐limiting toxicities were observed, and the target trough serum concentration was achieved in all patients at a dose of 18 mg/kg. Patritumab plus trastuzumab and paclitaxel was tolerable and efficacious at both doses, but we recommend the 18 mg/kg dose for future studies.